Answer:
A.(−1, −13) - yes
B.(−2, 9) - no
C.(3, 27) - no
D.(0, 1)- no
Step-by-step explanation:
Equation : ![f(x)=(13)x](https://tex.z-dn.net/?f=f%28x%29%3D%2813%29x)
We are supposed to find Which points are on the graph
So, the points which will satisfy the equation lies on the graph
A.(−1, −13)
x = -1
f(x)=-13
Substitute the points in graph
![f(x)=(13)x](https://tex.z-dn.net/?f=f%28x%29%3D%2813%29x)
![-13=(13(-1))](https://tex.z-dn.net/?f=-13%3D%2813%28-1%29%29)
![-13=-13](https://tex.z-dn.net/?f=-13%3D-13)
Since LHs = RHS
So, (−1, −13) is on the graph of ![f(x)=(13)x](https://tex.z-dn.net/?f=f%28x%29%3D%2813%29x)
B.(−2, 9)
x = -2
f(x)=9
Substitute the points in graph
![f(x)=(13)x](https://tex.z-dn.net/?f=f%28x%29%3D%2813%29x)
![9=(13(-2))](https://tex.z-dn.net/?f=9%3D%2813%28-2%29%29)
![-13\neq -26](https://tex.z-dn.net/?f=-13%5Cneq%20-26)
Since LHs≠RHS
So, (−2, 9) is not on the graph of ![f(x)=(13)x](https://tex.z-dn.net/?f=f%28x%29%3D%2813%29x)
C.(3, 27)
x = 3
f(x)=27
Substitute the points in graph
![f(x)=(13)x](https://tex.z-dn.net/?f=f%28x%29%3D%2813%29x)
![27=(13(3))](https://tex.z-dn.net/?f=27%3D%2813%283%29%29)
![27\neq 39](https://tex.z-dn.net/?f=27%5Cneq%2039)
Since LHs≠RHS
So, (3, 27) is not on the graph of ![f(x)=(13)x](https://tex.z-dn.net/?f=f%28x%29%3D%2813%29x)
D.(0,1)
x = 0
f(x)=1
Substitute the points in graph
![f(x)=(13)x](https://tex.z-dn.net/?f=f%28x%29%3D%2813%29x)
![1=(13(0))](https://tex.z-dn.net/?f=1%3D%2813%280%29%29)
![1\neq 0](https://tex.z-dn.net/?f=1%5Cneq%200)
Since LHs≠RHS
So, (0,1) is not on the graph of ![f(x)=(13)x](https://tex.z-dn.net/?f=f%28x%29%3D%2813%29x)